Kajian Antibakteri Ekstrak Etanol Kayu Secang (Caesalpinia sappan L.) dan Pemanfaatannya Pada Udang Vannamei (Liptopenaeus vannamei) Segar - Sastiani, Eka Z.; Murhadi , Murhadi; Suharyono, Suharyono; Sartika, Dewi; Yuliana , Neti (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Vannamei shrimp (Liptopenaeus vannamei) is a prominent fishery commodity due to its high consumption demand. However, susceptibility to bacterial damage and quality deterioration poses challenges. This study investigates the antibacterial potential of sappan wood extract in preserving shrimp shelf life. The research explores optimal extraction parameters, including solvent type and maceration duration, to assess yield percentage and antibacterial efficacy against Escherichia coli, Salmonella sp., and Vibrio parahaemolyticus. Utilizing a Complete Randomized Block Design (CRBD) in two phases, the study identifies 90% ethanol solvent and 6 hours maceration (P4M6) as the most effective treatment, yielding 7.32%. The extract addition significantly reduces shrimp microbial count, highlighting its potential in food preservation.